Efeito do ácido ursodesoxicólico e o papel da mucosa no desenvolvimento de dismotilidade esofagiana: estudo experimental com cobaias - Rocha, Marcelo Eustáquio Siqueira [UNIFESP] (2010)
Background and Aims: Esophageal motor abnormalities are frequently found in patients with gastroesophageal reflux disease. The role of bile in reflux-induced dysmotility is still elusive. Furthermore, it is questionable weather mucosal or muscular stimulation leads to motor modification. The aims of this study were: (a) analyze the effect of bile infusion in the amplitude of esophageal contractions and (b) analyze the effect of mucosal vs muscular stimulation. Methods: 18 guinea-pig esophagi were isolated and its contractility assessed with force transducers. Three groups were studied. In group A (n= 6) the entire esophagus was used and incubated in 100 ìML ursodeocycholic acid for 2 hours. In group B (n=6) the mucosal layer was removed and the muscular layer incubated in 100 ìML ursodeocycholic acid for 1 hours. In group C (n=6) (control group) the entire esophagus was used and incubated in saline solution. In all groups, five sequential contractions spaced by 1 minute were measured before and after incubation. Contractions were recorded after KCl 40 mM stimulation. Results: Contractions before incubation did differed among groups (p= 0,006) and averaged 1,319(A),0,306(B) and 1,795(C). After incubation amplitude of contraction was 0,709 , 0,278 and 1,353 for groups A, B and C respectively. Before incubation there were no diferrences between groups A and C (p=0,633) there was difference between groups A and B (p=0,039) and B and C (p=0,048). After incubation when we compare average within groups (before and after) there was difference only in group A (p=0,030). Conclusion: Our results show that bile exposure may induce ineffective esophageal motility and the mucosa seems to take an important role in esophageal motility. Disclosure Statement: No author has commercial associations that might create a conflict of interest. No competing financial interests exist.